Iron Deficiency Anemia in Pregnancy: Intravenous Versus Oral Route - Mehta, Meghana N; Shah, Jitesh M (National Journal of Community Medicine, 2014)
Background: The aim of this prospective, randomized, controlled study was to compare the efficacy of intravenous iron sucrose versus oral iron in the treatment of iron deficiency anemia during pregnancy. Methodology: One hundred fifty pregnant women with gestational age less than 34 weeks with iron deficiency anemia were selected. The women in group A received IV iron sucrose. The drug was administered by IV infusion. The women in the group B received ferrous sulphate as oral iron in the dose of two tablets three times a day. Repeat laboratory estimations were done after six weeks. Results were analyzed by t test and Z- test of preparation using SPSS 15 and Microsoft excel. Results: Mean gestational age in group A and group B were 26.13 ± 5.15 weeks and 26.27 ± 4.71 weeks, respectively. Mean Hb level was 6.71 ± 0.65 g/dl in group A which was raised to 10.64 ± 0.71 g/dl. Mean Hb level was 6.72 ± 0.67 g/dl in group B which was raised to 10.17 ± 0.54. The target Hb level of 10 g/dl was achieved in 88% cases in group A and in 76% cases in group B (P =0.055). Conclusion: Intravenous iron sucrose therapy is safe and as effective as oral iron in the treatment of iron deficiency anemia during pregnancy.